Development and field-testing of the Dementia Carer Assessment of Support Needs Tool (DeCANT). (3rd April 2021) - Clemmensen, Trine Holt; Kristensen, Hanne Kaae; Andersen-Ranberg, Karen; Lauridsen, Henrik Hein
ABSTRACT: Objectives: Caring for a person with dementia is associated with poor mental, physical, and social health, which makes it important to consider how carers are best supported in their caring role to preserve both their and the person with dementia's well-being. At present, a robust instrument to assess carers' support needs does not exist. This study aimed to develop a self-reported questionnaire to assess the support needs of carers of people with dementia. The objectives were to: (1) generate items, (2) pilot test, and (3) field-test the questionnaire. Design: Development and field-testing of a new questionnaire. Settings: Primary and secondary health and social care of informal carers and people with dementia in nine municipalities and one dementia clinic in a hospital in Denmark. Participants: Eight experts, 12 carers, and 7 digital users participated in pilot testing. 301 carers participated in field-testing. Measurements: Items for inclusion were generated based on interviews and literature review. An iterative process of data collection was applied to establish face and content validity of the Dementia Carer Assessment of Support Needs Tool (DeCANT) using Content Validity Index among experts and cognitive interviews with carers. Field-testing of DeCANT among carers included using the 12-item Short Form Health Survey, the Barthel-20 Index, and the Neuropsychiatric Inventory. Results: Initially, an item pool of 63 items was generated, and pilot testing reduced this to 42 items. Subsequent field-testing resulted in a 25-item version of DeCANT, and confirmatory factor analysis of three hypothesized models demonstrated a marginally better fit to a four-factor model with fit indices of: χ 2 = 775.170 ( p < 0.001), root mean square error of approximation = 0.073, Comparative Fit Index = 0.946, the Tucker-Lewis Index = 0.938, and weighted root mean residual (WRMR) = 1.265. Conclusions: DeCANT is a 25-item carer-reported questionnaire that can be used to help identify their support needs when caring for a person with dementia to enable supportive interventions and improve carers' health and well-being.